Analisis Kesadaran Konsumen Terhadap Labelisasi Halal Pada Makanan Instan Korea Bagi Mahasiswa Universitas Ibn Khaldun - Jilan Ashla Sayyidah; M. Kholil Nawawi; Nurman Hakim (Universitas Pahlawan Tuanku Tambusai, 2024)
Choosing halal food and drinks is an obligation for every Muslim. This applies in everyday life, including paying attention to the halal status of a product that will be consumed, one of which is by checking the halal information of the product on the packaging label. This study aims to determine the level of awareness of Ibn Khaldun University students towards Halal labeling in Korean instant food. The sample used in this study were 100 students of Ibn Khaldun University Bogor City. The method used in this study is quantitative by using data analysis techniques, namely univariate analysis techniques or commonly called descriptive statistical analysis techniques to determine and describe the data from the respondent's answer to the statement in answering the questionnaire. The results of this study indicate that students/female students as consumers of Korean instant food products have a high awareness or enter into a good category of halal labeling on the instant food